2016
DOI: 10.1039/c6ra17102h
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of zirconium in molten LiF–KF–ZrF4 at 600 °C

Abstract: The Zr electrochemical behavior was investigated in the LiF–KF–ZrF4 system and a multi-step redox mechanism was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…Indeed, during this step the nuclei develop diffusion zones around themselves, as the zones overlap the hemispherical mass transfer. This kinetics was also previously reported by Xu et al 22 Beyond the last step, the current density decays gradually over the time, which suggests the incessant synthesis of CICe alloys due to rise of the electroactive surface area. Among various models suggested to illustrate the CA curves for instantaneous and/or progressive nucleation of threedimensional (3D) hemispherical nuclei with growth rates controlled by ion volume diffusion (V d ) is the outstanding Scharier-Hills theoretical model.…”
Section: Resultssupporting
confidence: 87%
“…Indeed, during this step the nuclei develop diffusion zones around themselves, as the zones overlap the hemispherical mass transfer. This kinetics was also previously reported by Xu et al 22 Beyond the last step, the current density decays gradually over the time, which suggests the incessant synthesis of CICe alloys due to rise of the electroactive surface area. Among various models suggested to illustrate the CA curves for instantaneous and/or progressive nucleation of threedimensional (3D) hemispherical nuclei with growth rates controlled by ion volume diffusion (V d ) is the outstanding Scharier-Hills theoretical model.…”
Section: Resultssupporting
confidence: 87%
“…In fact, a previous study on Ni/YSZ/Ni cells showed that, above a critical voltage, the intermetallic compound Ni 3 Zr will form at the cathode interface . In a molten salt system, the reduction of Zr was found to be a multistep process including cathodic reactions of Zr 4+ /Zr 2+ , Zr 2+ /Zr + , and Zr + /Zr . By analogy, the reduction behavior of Zr in our study may follow a two-step mechanism corresponding to the two current plateaus, i.e., Zr 4+ → Zr 2+ /Zr + → Zr.…”
Section: Resultssupporting
confidence: 69%
“…32 In a molten salt system, the reduction of Zr was found to be a multistep process including cathodic reactions of Zr 4+ /Zr 2+ , Zr 2+ /Zr + , and Zr + /Zr. 33 By analogy, the reduction behavior of Zr in our study may follow a two-step mechanism corresponding to the two current plateaus, i.e., Zr 4+ → Zr 2+ /Zr + → Zr. Only two current plateaus appeared in the whole sweep even under higher potentials, and the device broke down at 9.1 V (equivalent to 14.8 MV/m), as shown in Figure S9a.…”
Section: ■ Introductionmentioning
confidence: 59%
“…Electrochemical approaches are especially attractive, as they allow a straightforward separation of the main components U, Pu and Zr (Murakami et al, 2009;Krishna et al, 2018). The main reaction media for those electrochemical separations are salt melts based on KCl and LiCl, or on KF and LiF that require high operating temperatures of at least 773 K (Xu et al, 2016;Quaranta et al, 2018). Lower temperatures would be highly beneficial for the overall process and would make the electrochemical processing of those spent nuclear fuels significantly more facile.…”
Section: Introductionmentioning
confidence: 99%